Assessment of the current state of commodity circulation in the Russian Federation (Nexo Revista Científica, 2022)
This article presents the results of a study of the current state of the sphere of commodity circulation in the Russian Federation as part of the market economy and economic relations taking place in it. The process, system, situational methods of analysis were applied, which allowed identifying the main elements of the sphere of commodity circulation (commodity movement in the form of direct sales or wholesale trade, circulation of goods carried out by retail enterprises and organizations, cooperative activities for the purchase and sale of products), problems of the development of the sphere of circulation, including the uneven development of the transport network (especially at the level of such regions as the Far East, the Volga region), the underdevelopment of the market of wholesale distribution centers and the lack of federal platforms for effective redistribution of products between regions, its packaging, storage and transportation, customs services, lack of coordination of actions and adaptive abilities between economic entities in the sphere of commodity circulation. The authors have identified areas for improving the competitiveness of organizations in the sphere of commodity circulation, including the development of the logistics market of wholesale and distribution centers.